Spatial Variability of the Characteristics of Coral Coverage in the Waters of North Seribu Islands District, DKI Jakarta: Variabilitas Spasial Karakteristik Tutupan Karang di Perairan Kecamatan Kepulauan Seribu Utara, DKI Jakarta - Qonita Sinatrya; Damar, Ario; Wulandari, Dwi Yuni (Habitus Aquatica, 2024)
Coral reefs take a long time to recover and prone to damage. This study aims to analyze the spatial variability of coral reef coverage based on different utilization categories in the Waters of the North Seribu Islands District. This study was conducted in North Seribu Islands District that divided into six sampling points in August 2022. The coral coverage data collection was estimated using the Line Intercept Transect method, the water quality samples taken were brightness, nitrate, dissolved oxygen, pH, and salinity. Different utilization categories between sampling stations have no significant effect on coral cover percentage, except for protected categorized station. The main cause affecting the coral coverage is suspected to be due to physical damage caused by direct impacts from human activities, such as fishing, tourism, and transportation activities. The highest coral coverage in the good category was in the Marine Protected Area, while the lowest coral coverage in the damaged category was in West Pramuka Island as the location most affected by human activities.